a) Express 4(cosec^2(2x)) - (cosec^2(x)) in terms of sin(x) and cos (x) and hence b) show that 4(cosec^2(2x)) - (cosec^2(x)) = sec^2(x)

A) 4(cosec2(2x)) - (cosec2(x)) = 4/(sin2(2x)) - 1/(sin2(x)) = 4/[(2 sin(x) cos(x))2] - 1/(sin2(x)) B) 4/[(2 sin(x) cos(x))2] - 1/(sin2(x)) = 4/(4 sin2(x) cos2(x)) - 1/(sin2(x)) = 1/(sin2(x) cos2(x)) - cos2(x)/[sin2(x)cos2(x)] = {Using 1 - cos2(x) = sin2(x)} = sin2(x)/(sin2(x)cos2(x)) = 1/(cos2(x)) = sec2(x)

Answered by Mario R. Maths tutor

17401 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

A tunnel has height, h, (in metres) given by h=14-x^2 where x is the horizontal distance from the centre of the tunnel. Find the cross sectional area of the tunnel. Also find the maximum height of a truck passing through the tunnel that is 4m wide.


A circle with centre C has equation x^2 + y^2 + 2x + 6y - 40 = 0 . Express this equation in the form (x - a)^2 + (x - b)^2 = r^2. Find the co-ordinates of C and the radius of the circle.


Where does the circle (x-6)^2+(y-7)^2=4 intersect with y=x+3


Derive the quadratic equation.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences